Epidemiology characteristics of the drinking patterns and alcohol consumption among adults in Hainan Province, China - Ou, Tingting; Jiang, Juan; Sun, Dingwei; Liu, Ying; Xiong, Changfu; Wang, Xiaohuan; Zhou, Xue; Wu, Hongying; Zhang, Lijie; Wang, Chao; He, Bin (Frontiers in Public Health, 2025)
BackgroundAlcohol consumption is a significant risk factor for premature mortality and increased disease burden worldwide, especially among young and middle-aged individuals. This study aims to evaluate drinking patterns and alcohol consumption among adults in Hainan Province, while also identifying associated factors.MethodsAnalyses based on the 2022 “2 + 3” epidemiological survey in Hainan were conducted, and the drinking types, quantities, and frequencies among local residents were described. Chi-square tests and multiple linear regression were employed for the statistical analysis.ResultsA total of 32,857 adults participated, yielding an overall drinking rate of 42.8%. The drinking rate was significantly higher among men (64.4%) than women (18.9%). The highest drinking rates were found in the 30–59 age group, especially among individuals aged 30–39. Ethnic minorities had a higher drinking rate (70.1%) than Han individuals. Lower educational attainment was associated with lower drinking rates, although the prevalence of active drinkers was higher. Men preferred strong liquor and beer, whereas women favored beer and rice wine. The average weekly alcohol consumption was 59.8 mL for men and 10.9 mL for women, with 43.6% of men exceeding 100 mL weekly, compared to 12.7% of women.ConclusionThis study emphasizes the complexity and diversity of drinking behaviors among adults in Hainan Province. Sociodemographic factors, including gender, age, ethnicity, education, marital status, occupation, and region, are closely linked to drinking behaviors. The findings provide a scientific basis for developing targeted public health strategies, highlighting the need for effective interventions to mitigate alcohol-related health issues among high-risk populations.